Příslovečné určení v literárních textech a v knižních recenzích - Černá, Kamila Emma (Univerzita Pardubice, 2020)
This bachelor thesis deals with adverbials, particularly adjuncts and subjuncts, occurring in literary texts and in book reviews. The first chapter introduces adverbials in general along with their functions, positions and syntactic forms. Then the two following chapters focus respectively on adjuncts and subjuncts. In both chapters, each type of adverbial is explained in detail along with its semantic categories, which are also thoroughly described. The theoretical part is concluded with a brief introduction into the literary style and the style of book reviews. The aim of the practical part is to analyse corpus findings and interpret them with respect to their functions, positions, realizations and the type of register.
Adverbials in Literary Texts and Book Reviews
Keywords: adverbials; adjuncts; subjuncts; book reviews; literary style; příslovečná určení; adjunkty; subjunkty; knižní recenze; literární žánr